Mitochondrial Dynamics and the ER: The Plant Perspective - Mueller, Stefanie J.; Reski, Ralf (Frontiers in Cell and Developmental Biology, 2015)
Whereas contact sites between mitochondria and the ER have been in the focus of animal and fungal research for several years, the importance of this organellar interface and the molecular effectors are largely unknown for plants. This work gives an introduction into known evolutionary differences of molecular effectors of mitochondrial dynamics and interactions between animals, fungi and plants. Using the model plant Physcomitrella patens, we provide microscopic evidence for the existence of mitochondria-ER interactions in plants and their correlation with mitochondrial constriction and fission. We further investigate a previously identified protein of unknown function (MELL1), and show that it modulates the amount of mitochondrial association to the ER, as well as mitochondrial shape and number.